2008
DOI: 10.1016/j.cub.2007.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas syringae Effector AvrPto Blocks Innate Immunity by Targeting Receptor Kinases

Abstract: Plants use receptor kinases, such as FLS2 and EFR, to perceive bacterial pathogens and initiate innate immunity. This immunity is often suppressed by bacterial effectors, allowing pathogen propagation. To counteract, plants have evolved disease resistance genes that detect the bacterial effectors and reinstate resistance. The Pseudomonas syringae effector AvrPto promotes infection in susceptible plants but triggers resistance in plants carrying the protein kinase Pto and the associated resistance protein Prf. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
383
2
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 415 publications
(403 citation statements)
references
References 36 publications
6
383
2
6
Order By: Relevance
“…Binding of AvrPto by Pto might then interfere with the ability of the effector to disrupt PTI (Xing et al, 2007). Indeed, it was shown recently that AvrPto interacts with the kinase domains of both FLS2/EFR1 from Arabidopsis and inhibits their kinase activity that is needed for PTI (Xiang et al, 2008). Moreover, both the FLS2 kinase domain and Pto bind AvrPto in a competitive manner, supporting structural similarity between FLS2-AvrPto and Pto-AvrPto interaction (Xiang et al, 2008).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Binding of AvrPto by Pto might then interfere with the ability of the effector to disrupt PTI (Xing et al, 2007). Indeed, it was shown recently that AvrPto interacts with the kinase domains of both FLS2/EFR1 from Arabidopsis and inhibits their kinase activity that is needed for PTI (Xiang et al, 2008). Moreover, both the FLS2 kinase domain and Pto bind AvrPto in a competitive manner, supporting structural similarity between FLS2-AvrPto and Pto-AvrPto interaction (Xiang et al, 2008).…”
Section: Introductionmentioning
confidence: 88%
“…Indeed, it was shown recently that AvrPto interacts with the kinase domains of both FLS2/EFR1 from Arabidopsis and inhibits their kinase activity that is needed for PTI (Xiang et al, 2008). Moreover, both the FLS2 kinase domain and Pto bind AvrPto in a competitive manner, supporting structural similarity between FLS2-AvrPto and Pto-AvrPto interaction (Xiang et al, 2008). Interestingly, AvrPto also appears to bind BAK1 (Shan et al, 2008), a protein required for FLS2 and EFR1 function (Chinchilla et al, 2007;Heese et al, 2007).…”
Section: Introductionmentioning
confidence: 89%
“…It has been revealed that mutation in FeRONIA (FeR), a CrRLK, leads to spontaneous H 2 O 2 production and cell death, resulting in PM resistance and aberrant pollen tube reception (Kessler et al 2010). Interaction of another related RLK, At2g23200 in yeast two-hybrid assays with the Pseudomonas syringae effector AvrPto showed that its expression was regulated by a number of PAMPs, pathogen-secreted molecules that regulate infection and triggers immunity (Xiang et al 2008). ANXUR 1 and ANXUR 2 which are RLKs help in cell wall integrity and are homologous to FeR, but have opposite functions to FeR (Boisson-Dernier et al 2009;Miyazaki et al 2009).…”
Section: Auxinmentioning
confidence: 99%
“…T3Es commonly contain sequences addressing specific eukaryotic subcellular localizations (10,11) and enzymatic activities (12)(13)(14)(15)(16)(17) that disrupt and/or suppress PTI. Known targets of T3Es include plasma membrane-localized receptor complexes (13,(18)(19)(20)(21)(22)(23), downstream MAPK cascades (24,25), the stability of defenserelated transcripts (26), phytoalexin biosynthesis (27), and vesicle trafficking (28).…”
mentioning
confidence: 99%